Literature Review: The Potential of Turkey (Meleagris gallopavo) as a Meat Producer - Tamzil, Mohammad Hasil (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The turkey (Meleagris gallopavo) is a large poultry species with unique phenotypic diversity, exotic characteristics, and distinctive meat flavor. Globally, it has been recognized as an important source of high-quality animal protein with relatively lowfat content. In Indonesia, turkey farming remains underdeveloped despite its considerable potential as an alternative meat source. This study is a literature review that synthesizes scientific findings from various references related to the domestication, distribution, and meat production potential of turkeys. Domestic turkeys are descendants of the wild turkey (M. gallopavo gallopavo), first domesticated in Central Mexico and parts of the United States. From there, domesticated stocks were introduced to Europe via Spanish colonial routes and subsequently spread worldwide. In Indonesia, turkeys have shown promising adaptability and potential for meat production. However, their development is hindered by limited access to high-quality breeding stocks, both in terms of quantity and genetic improvement. Turkeys possess significant potential to serve as an alternative poultry species for meat production in Indonesia. Addressing constraints in breeding stock availability and improving genetic resources are essential steps toward optimizing their productivity and sustainability.